Macroautophagy inhibition maintains fragmented mitochondria to foster T cell receptor‐dependent apoptosis. (7th July 2016) - Corrado, Mauro; Mariotti, Francesca R; Trapani, Laura; Taraborrelli, Lucia; Nazio, Francesca; Cianfanelli, Valentina; Soriano, Maria Eugenia; Schrepfer, Emilie; Cecconi, Francesco; Scorrano, Luca; Campello, Silvia
Abstract: Mitochondrial dynamics and functionality are linked to the autophagic degradative pathway under several stress conditions. However, the interplay between mitochondria and autophagy upon cell death signalling remains unclear. The T‐cell receptor pathway signals the so‐called activation‐induced cell death (AICD) essential for immune tolerance regulation. Here, we show that this apoptotic pathway requires the inhibition of macroautophagy. Protein kinase‐A activation downstream of T‐cell receptor signalling inhibits macroautophagy upon AICD induction. This leads to the accumulation of damaged mitochondria, which are fragmented, display remodelled cristae and release cytochrome c, thereby driving apoptosis. Autophagy‐forced reactivation that clears the Parkin‐decorated mitochondria is as effective in inhibiting apoptosis as genetic interference with cristae remodelling and cytochrome c release. Thus, upon AICD induction regulation of macroautophagy, rather than selective mitophagy, ensures apoptotic progression. Synopsis: Activation‐induced cell death (AICD) in T lymphocytes is essential for immune tolerance regulation. AICD relies on autophagy inhibition, mitochondrial fragmentation and cristae remodelling, which result in the accumulation of dysfunctional mitochondria and consequent release of pro‐apoptotic factors. Upon AICD induction, mitochondria fragment, cristae are remodelled and cytochrome c release is amplified. Early upon T‐cell receptor restimulation, macroautophagy is inhibited, though Parkin translocates to fragmented mitochondria. The PKA–AMPK axis mediates inhibition of autophagy during AICD. Pharmacological or genetic reactivation of autophagy during AICD removes Parkin‐decorated mitochondria and reduces apoptosis. Genetic depletion of autophagy promotes efficient AICD in vivo . Abstract : Activation‐induced cell death (AICD) in T lymphocytes is essential for immune tolerance regulation. AICD relies on autophagy inhibition, mitochondrial fragmentation and cristae remodelling, which result in the accumulation of dysfunctional mitochondria and consequent release of pro‐apoptotic factors.